(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Classification of diabetes is an area of major concern in the field of medical science. Diabetes is not a single disease rather a group of health disorders that is hazardous to human health if not detected on time. Diabetes can be classified under three classes based on blood glucose level(BG): hyperglycemia(BG≥180mg/dL), hypoglycaemia (≤70 mg/dL) and euglycaemia (>70 and